Production of Miso-like Products using Local Grain Legumes - Gbeddy, D.V. (University of Ghana, 2001)
Miso is a semi-solid fermented food made commonly in Japan from soybeans alone or from a mixture of soybeans and rice or barley. This was a study to determine the suitability of local grain-legumes in the production of miso-\\ke products. A traditional two-step fermentation process was adapted to process peanuts, cowpea and soybeans into the mso-like products. Three products were formulated with the legume combinations of peanut-cowpea, peanut-soybean and cowpea-soybean in ratios of 1:1. Rice koji was prepared with spores of Aspergillus oryzae. Miso sample obtained from Japan was used as an inoculum. The mixtures were fermented for a period of 60 days at 35°C The moisture content and pH values of the fermenting mass decreased whilst the total acid, lipid, free amino nitrogen, total soluble nitrogen and protein contents increased with fermentation time. These increases were very rapid during the first 10 days of fermentation. Major groups of microorganisms involved in the fermentation were mold, yeast and lactic acid bacteria. Although the total plate counts varied during the fermentation period, the final microbial populations were not significantly different from the initial counts. Total microbial population of the three products varied in the range of 104 - 106 cfu/g. The highest count was observed in the cowpea-soybean sample, 2.2 x 106 cfu/g after 4 days of fermentation. The main microorganisms isolated from the fermenting mass were of the genera Streptococcus, Staphylococcus, Micrococcus and Pediococcus. The dominant species that persisted throughout the fermentation period were the Micrococcus and Pediococcus species. The mold population decreased while that of the yeast and lactic acid bacteria increased initially before gradually coming down with fermentation time. Proximate composition of the dehydrated samples were in the range of 4.4 - 5.9 % for moisture, 24.9 - 32.6 % for protein, 10.5 - 32.2 % for total lipids, 19.5 -25.0 % for ash, 1.17 - 1.3 % for fiber. Total carbohydrates as determined by subtraction were in the range 13.7 - 25.1 %. The highest amount of protein, ash and reducing sugars were found in the cowpea-soybean product. Functional properties of the products were found to be suitable for formulating into soups and stews. Water absorption capacity was in the range of 557 - 793 g/kg, fat absorption 439 - 532 g/kg, swelling capacity 12.5-29.4 %, foaming ability 1.5 - 5.5 %, emulsifying capacity 57.8 - 67.4 % and emulsion stability of 58 - 65.4 %. All the three products remained very stable at room temperature when stored over a period of 12 weeks. The amount of free fatty acids (FFAs) and peroxides (PV) formed in the samples during the 12-week storage were below 0.4 % and 4 mEq/kg, respectively. Thiobarbituric reactive substances (TBA) formed in the peanut-cowpea sample was in the range of 0.006 - 0.02 mg malonaldehyde/kg of sample. The TBA values decreased significantly with storage time. Sensory analysis revealed the cowpea soybean as the most acceptable of the three samples. The observed changes and characteristics of the products suggest that local grain-legumes may be suitable for processing into /miso-like products.
Thesis (MPhil) - University of Ghana.